Width of the charge-transfer peak in the SU(N) impurity Anderson model and its relevance to nonequilibrium transport - Fernández, Joaquín (2018)
We calculate the width 2ΔCT and intensity of the charge-transfer peak (the one lying at the on-site energy Ed) in the impurity spectral density of states as a function of Ed in the SU(N) impurity Anderson model (IAM). We use the dynamical density-matrix renormalization group (DDMRG) and the noncrossing approximation (NCA) for N=4 and a 1/N variational approximation in the general case. In particular, while for Ed Δ, where Δ is the resonant level half-width, ΔCT=Δ as expected in the noninteracting case, for Ed NΔ one has ΔCT=NΔ. In the N=2 case, some effects of the variation of ΔCT with Ed were observed in the conductance through a quantum dot connected asymmetrically to conducting leads at finite bias [J. Könemann, Phys. Rev. B 73, 033313 (2006)PRBMDO1098-012110.1103/PhysRevB.73.033313]. More dramatic effects are expected in similar experiments that can be carried out in systems of two quantum dots, carbon nanotubes or other, realizing the SU(4) IAM.